PENERAPAN PENDEKATAN SUPERVISI NON DIREKTIF DALAM MENINGKATKAN KEMAMPUAN GURU MENGGUNAKAN MEDIA PEMBELAJARAN DI SD NEGERI 1 CAKRANEGARA - SETIAWATI, NI NYOMAN ELLY (Universitas Mahasaraswati Mataram, 2018)
From the results of the monitoring of the researchers it turns out that the implementation of learning from the teachers there are still 3 teachers who do not use learning media on the grounds of difficulty getting media and the inability of teachers to use the media in the learning process, thus impacting the low motivation and learning outcomes of students.This study aims to determine whether the application of a non-directive supervision approach can improve the ability of teachers to use media in SD Negeri 1 Cakranegara in the 2016/2017 school year. The subjects of the study were 1 grade 6, 5 and 4 teachers.Data collection techniques using observation, evaluation and documentation. The collected data were analyzed descriptive qualitative.The results showed that: the application of a non-directive supervision approach can improve the teacher's ability to use character card media. This can be seen as follows: 1) For subject A in cycle I for the preparation value 83 in cycle II to 95, an increase of 12%, the use of media from 65 to 85 increased by 20%, while for the average overall PBM cycle I 72 and on the cycle II became 91 with an increase of 19%. 2) For subject B in cycle I for preparation value 80 in cycle II to 93, an increase of 13%, the use of media from 60 to 90 increased by 30%, while for the overall average PBM cycle I 68 and in cycle II it became 91 with an increase of 23% . 3) For C subjects in cycle I for the preparation value 85 in cycle II to 93, an increase of 8%, the use of media from 60 to 90 increased by 30%, while for the overall average PBM cycle I 71 and in cycle II it became 94 with an increase of 23%.